PARADIGMA LEGITIMASI HUKUM KONTEMPORER: INTERGRASI VALIDITAS FORMAL, JUSTIFIKASI MORAL, DAN PENERIMAAN SOSIAL DALAM PERSPEKTIF OTORITAS HUKUM JOSEPH RAZ - Akhmad Qadar Ramadhan; Daffin Ramadhan Pradiza; Muhammad Ridho Gunawan; Surya Indra Danuarta; Elviandri Elviandri (CV. Denasya Smart Publisher, 2026)
This study aims to analyze Joseph Raz's concept of legal authority through the Service Conception of Authority and examine its relevance to inclusive legal positivism in reconstructing contemporary legal legitimacy. The study is motivated by the growing crisis of legal legitimacy, reflected in declining public trust in legal institutions and the widening gap between the formal validity of law and its social acceptance. This research employs a normative legal research method using both a conceptual approach and a statute approach. Primary, secondary, and tertiary legal materials are analyzed qualitatively using a descriptive-analytical method. The findings indicate that legal legitimacy, according to Joseph Raz, depends not only on the formal validity of legal rules but also on the law's ability to provide individuals with better practical reasons for action through the dependence thesis, normal justification thesis, and pre-emption thesis. Inclusive legal positivism broadens the concept of legal validity by recognizing the role of moral values in determining legal validity. This study concludes that contemporary legal legitimacy should be reconstructed through the integration of formal validity, moral justification, and social acceptance, thereby producing a more adaptive and sustainable model of legal legitimacy for modern legal systems.